Working With the News Media - Ricky Telg (EDIS, 2011)
Learn to think like a reporter about what stories are newsworthy and how you can help them do their job better and get your message out to the public. This 3-page fact sheet was written by Ricky Telg, and published by the UF Department of Agricultural Education and Communication, August 2011.